Low-cost synthesis of α-Fe2O3 nanorods for photocatalytic application - Luong, Hoai Nhan; Nguyen, Le Ngoc Thu; Dinh, Tan Muon; Dinh, Nguyen Dan Nhi; Le, Thai Duy; Tran, Cong Khanh; Dang, Vinh Quang (Science & Technology Development Journal, 2024)
Introduction: α-Fe2O3 nanorods (α-Fe2O3 NRs), also known as hematite, possess a narrow band gap, high chemical stability, extensive surface area, controllable size, and outstanding photoelectric properties. These attributes make hematite a promising material for various applications, including gas sensors, optical sensors, and notably, photocatalysis. In previous studies, α-Fe2O3 nanorods were synthesized using various processes. However, these processes involve extensive use of precursors, are expensive, and time-consuming, and have negative impacts on the environment. Hence, this investigation introduces an uncomplicated, efficient, and high-precision hydrothermal process for synthesizing α-Fe2O3 nanorods (α-Fe2O3 NRs). Methods: We utilized a short-term hydrothermal process to synthesize α-Fe2O3 nanorods. Characterization of the nanorods involved XRD, VESTA, Raman, SEM, and EDX to examine their morphology and structure, with UV-Vis spectroscopy used to determine their absorption spectra. The photocatalytic efficiency of the α-Fe2O3 nanorods was assessed by their ability to degrade methylene blue dye at a concentration of 2.5 ppm. Results: VESTA simulations and XRD patterns confirmed that the α-Fe2O3 nanorods have a rhombohedral crystal structure and belongs to space group R3 ̅c. The optical bandgap was determined to be 2.2 eV through calculations using Tauc’s method. Through scanning electron microscopy (SEM), the average length and diameter of the α-Fe2O3 NRs were determined to be 415 nm and 110 nm, respectively. The photocatalytic capacity for degrading methylene blue (concentration of 2.5 ppm) was 55%. Conclusion: This exploration of the fundamental characteristics of α-Fe2O3 NRs offers deeper insights into the properties of nanorod-structured hematite materials. Moreover, the synthesis of α-Fe2O3 NRs using this hydrothermal method addresses several previously identified challenges, thereby contributing to broadening the potential applications of α-Fe2O3 NRs across various fields in the future.